Thermal fluid activities along the Mozumi-Sukenobu fault, central Japan, identified via zircon fission-track thermochronometry - Sueoka, Shigeru; Ikuho, Zuitetsu; Hasebe, Noriko; Murakami, Masaki; Yamada, Ryuji; Tamura, Akihiro; Arai, Shoji; Tagami, Takahiro (Journal of Asian Earth Sciences: X, 2019)
•Thermal anomaly across a fault deduced from zircon fission-track thermochronometry.•Two reheating episodes at ∼60 Ma and ∼30–15 Ma in and around the fracture zones.•Paleocene reheating by advection of thermal fluids from the Kamioka Mine region.•Miocene reheating related to magmatism during opening of the Sea of Japan. This study uses zircon fission-track (ZFT) thermochronometry to investigate thermal anomalies along the Mozumi-Sukenobu fault, central Japan, and assesses the most plausible mechanisms by which reheating events occurred. In total, 14 samples were collected from Mesozoic sedimentary rocks along a research tunnel excavated across the fault. The mean ZFT ages range from 110.3 to 73.3 Ma, whereas the mean ZFT lengths are 7.1–9.0 μm. Thermal histories estimated by inverse modeling based on the ZFT data indicate two reheating episodes at ∼60 Ma and ∼30–15 Ma. The reheating episode at ∼60 Ma was detected from two samples collected from between the two major fracture zones. This episode can be attributed to thermal fluids sourced from the Kamioka Mine region in the south on the basis of the timing of the event and the presence of minerals produced via hydrothermal alteration. Reheating at ∼30–15 Ma is indicated in majority of the samples. This is thought to be related to magmatism associated with the opening of the Sea of Japan, but the source and mechanism of reheating cannot be clearly determined. Reheating is not attributable to simple thermal diffusion from volcanic products deposited at the surface. The spatial pattern of the thermal anomalies can be explained by the dextral slip along the two major fracture zones since the late Quaternary. Although the identified thermal episodes are background events potentially related to fluid activities, they are important for quantifying thermal history along the fault zone including the frictional heating.